THE INFLUENCE OF SERVICE QUALITY ON PATIENT LOYALTY THROUGH PATIENT SATISFACTION AT RSUD DR. CHASBULLAH ABDULMADJID IN BEKASI CITY - Gladdays Naurah; Kosasih; Laili Rahmiyati (RADJA PUBLIKA, 2025)
This study aims to obtain empirical evidence on the influence of service quality on patient loyalty, with patient satisfaction as an intervening variable. The research locus is RSUD Dr. Chasbullah Abdulmadjid in Bekasi City. The research method used is descriptive-verificative analysis and panel data regression analysis (pathway analysis), with data collection techniques using questionnaires distributed to 100 outpatients in the general and BPJS categories. The descriptive analysis results indicate that service quality, patient satisfaction, and patient loyalty are generally classified as good. The verificative analysis results confirm that service quality significantly enhances patient loyalty, as well as service quality influencing patient satisfaction and patient satisfaction affecting patient loyalty. There is an influence of service quality on patient loyalty through patient satisfaction at RSUD Dr. Chasbullah Abdulmadjid in Bekasi City. Patient satisfaction is not only a supporting factor but also plays a role in strengthening the relationship between service quality and patient loyalty